2015
DOI: 10.1155/2015/890508
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cortical Maturation in a Child with Cochlear Implant: Analysis of Electrophysiological and Behavioral Measures

Abstract: The purpose of this study was to longitudinally assess the behavioral and electrophysiological hearing changes of a girl inserted in a CI program, who had bilateral profound sensorineural hearing loss and underwent surgery of cochlear implantation with electrode activation at 21 months of age. She was evaluated using the P1 component of Long Latency Auditory Evoked Potential (LLAEP); speech perception tests of the Glendonald Auditory Screening Procedure (GASP); Infant Toddler Meaningful Auditory Integration Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…CAEP testing has shown that P1 latency decreases substantially after cochlear implant activation. These authors also report that earlier timing of activation (before age 2 years) is associated with greater likelihood of normal cortical responses, improved speech perception, and greater development of hearing skills and oral language (28) .…”
Section: Discussionmentioning
confidence: 86%
“…CAEP testing has shown that P1 latency decreases substantially after cochlear implant activation. These authors also report that earlier timing of activation (before age 2 years) is associated with greater likelihood of normal cortical responses, improved speech perception, and greater development of hearing skills and oral language (28) .…”
Section: Discussionmentioning
confidence: 86%